Current and capacitor-voltage balancing controls of three-level buck converter - Udomkaew, Srimongkhon; Sengsui, Krittayot; Saksiri, Wiset; Gavagsaz-Ghoachani, Roghayeh; Phattanasak, Matheepot; Pierfederici, Serge (2023 Research, Invention, and Innovation Congress: Innovative Electricals and Electronics (RI2C), 2023)
This paper presents a control method for the three-level buck converter. The primary objective of this study is to control the inductor current to satisfy the requirements for tracking and regulation. Additionally, considering non-ideal components and the switching command signal, which includes switch drivers, it is possible for the voltage across each input capacitor to be unequal. Such a situation could lead to converter malfunctions. Therefore, the second goal is to achieve balancing of the input capacitor voltages. A nonlinear control approach is employed to control the current of the output inductor and the voltage across the input capacitors. The effectiveness of the proposed control method, along with its robustness properties against variations in passive devices, is demonstrated through MATLAB/Simulink simulations.